Short-term outcomes of da Vinci Xi versus Si robotic systems for minor hepatectomies - Bianchi, Giorgio; de'Angelis, Nicola; Musa, Nicola; Beghdadi, Nassiba; Hentati, Hassen; Ammendola, Michele; Inchingolo, Riccardo; Laurent, Alexis; Sommacale, Daniele; Memeo, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
Background: In the recent years, robotic technology has been drastically improved and the last generation of robotic platforms is hardly comparable with the earlier ones. The present study aims to investigate the short-term outcomes of minor hepatectomies performed with da Vinci Xi surgical system vs. Si surgical systems.Methods: Consecutive patients operated on between 2013 and 2020 in two referral centers were selected if underwent elective robotic minor hepatectomy (